Formulation of Strategy for Sustainable Empowerment of The Fishing Community at Makasar Island Baubau City Indonesia - Tanzil (CV. Literasi Indonesia, 2024)
This research aims to formulate a strategy for sustainably empowering fishing communities. This research uses a qualitative approach, namely research that emphasizes more aspects of an in-depth understanding of a research object. This research was conducted on Makassar Island, Baubau City Indonesia, where most of the population has a livelihood as fishermen. This research uses informants from fishermen, community leaders, and local government officials. To obtain these informants, purposive techniques are used, where informants are selected based on their ability to provide in-depth information. This study used several data collection techniques, namely observation, interviews, documentation, and focused group discussion. Data analysis in this study uses SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats. The results of the study obtained several formulations of strategies for empowering fishing communities as follows: first, community-based empowerment of fishing communities; second, strengthening fishermen institutions; third, capital access development; fourth, mastery of fishing technology; and fifth, improve the technical capabilities of professional fisheries extension workers. This study recommends that the empowerment of fishing communities in Makassar Island should be directed at community-based empowerment. This approach sees that various social problems that exist in the fishing community are not only caused by problems that arise in the fishing community internally but also caused by various structural problems. This approach is also very aware of the importance of capacity building in fishing communities to increase the strength and independence of fishing communities.